Back Cover: Microwave spectroscopy on heavy‐fermion systems: Probing the dynamics of charges and magnetic moments (Phys. Status Solidi B 3/2013). Issue 3 (14th March 2013) - Scheffler, Marc; Schlegel, Katrin; Clauss, Conrad; Hafner, Daniel; Fella, Christian; Dressel, Martin; Jourdan, Martin; Sichelschmidt, Jörg; Krellner, Cornelius; Geibel, Christoph; Steglich, Frank
<x xml:space="preserve">Abstract</x> The electronic properties of heavy‐fermion metals are governed by mobile charge carriers with drastically enhanced effective masses. Correspondingly, the characteristic energy scales of their optical response are much lower than for conventional metals: the transport relaxation of heavy fermions can be as low as a few GHz. Signatures of heavy‐fermion superconductivity and quantum criticality are also found or at least expected in this frequency range. To probe these charge dynamics at extremely low frequencies, novel techniques of microwave spectroscopy have to be employed. As described by Scheffler et al. (pp. 439–449), devices based on planar microwave transmission lines are a powerful approach for this goal. Such experiments reveal the frequency‐dependent conductivity (i.e. the charge response), but they can also be used to study spin dynamics via electron spin resonance (ESR). This opens new possibilities to experimentally explore the spin dynamics of the heavy‐fermion material YbRh2Si2 throughout its phase diagram including the vicinity of the quantum‐critical point. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>